1995
DOI: 10.1017/s0033822200030551
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Shells and Foraminifera from the Skagen Core, Denmark: Evidence of Reworking

Abstract: ABSTRACT. We report on 69 radiocarbon dates of mollusk shells and benthic foraminifera from the upper 132 m of the marine shelf sediments of the Skagen Core (220 m total length). The dated sequence covers the Late Glacial and the Holocene (from 15 ka BP to Recent). Sedimentation rates range from 1 to 70 m ka'1. The macrofossil shell dates follow a smooth curve constituting an age model for dating the sediments. The foraminiferal dates fall into two groups: those that agree exactly with the mollusk shells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…Where possible, paired foraminifera and bivalve ages were measured. In another study covering a similar time interval (Lateglacial to Holocene) in Denmark, where paired ages have been measured, foraminifera yielded systematically older ages than molluscs (Heier‐Nielsen et al 1995). The authors concluded that the age discrepancies resulted from reworking of the foraminifera (probably by lateral transport of older fossil material) and that mollusc ages are more reliable when attempting to date sediments.…”
Section: Chronology and Age Modelsmentioning
confidence: 97%
“…Where possible, paired foraminifera and bivalve ages were measured. In another study covering a similar time interval (Lateglacial to Holocene) in Denmark, where paired ages have been measured, foraminifera yielded systematically older ages than molluscs (Heier‐Nielsen et al 1995). The authors concluded that the age discrepancies resulted from reworking of the foraminifera (probably by lateral transport of older fossil material) and that mollusc ages are more reliable when attempting to date sediments.…”
Section: Chronology and Age Modelsmentioning
confidence: 97%
“…Freshwater may contain dissolved CaCO 3 from fossil carbonate in soils. The freshwater reservoir age is known to vary considerably with time and location (Heier-Nielsen et al 1995;Lanting and van der Plicht 1998;). Hence individuals who subsisted or partly subsisted on marine or freshwater diets are often very difficult to date directly by their bone remains (Lanting and van der Plicht 1998;Arneborg et al 1999;Bonsall et al 2004;Fischer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This will directly affect AMS dating with measured ages older than true ages, as observed within the transgressive seismic unit U500. Such phenomena have been observed in Denmark (Heier-Nielsen et al, 1995) and Spain (Cearreta and Murray, 2000), and these highlight the difficulty to obtain reliable AMS dates from high-energy transgressive deposits. Within the most recent prograding units of the highstand systems tract (4.5 to 0.3 ka cal.…”
Section: Benthic Meiofauna Reworking Processes In Subaqueous Deltaic mentioning
confidence: 89%